Volatilidade e correlações condicionais no mercado de ações em períodos de crise - Borges, Wemerson Gomes (2020)
This study aims to investigate the movements and contagions in Latin American stock markets in an environment of high volatility, testing the benefits of diversification in times of crisis. the subprime crisis being analyzed for latin america and in the specific case of brazil the crisis started in 2014 due to corruption events. In order to achieve this objective, the research sought to identify the behavior of the dynamic correlations of the sectors of the main markets of Latin America and particularly in the Brazilian domestic market in relation to the North American stock market, in periods of crisis. The sample is composed of stock indexes, broad and dollarized, from Brazil, Mexico, Chile, Argentina and the United States (only the S&P500). The period investigated was from January 2000 to December 2018. A period that covers a subprime crisis that affected all the countries in question, thus being a sample that uses a period of crisis and not a conditional correlation assessment. To test the correlations, it used the Asymmetric Dynamic Conditional Correlation (ADCC) models. The results indicate that in general the correlations increase in periods of crisis in all markets and sectors, thus reducing the benefits of portfolio diversification in these periods. It was also possible to observe that the increase in correlations during an internal crisis is of lesser magnitude than the increase in correlations during external crises, such as Subprime. However, in the case of sector analyzes, indices with low correlations, were observed possible options for investors in protection portfolios: Basic materials sector in Brazil, telecommunications in Mexico, utilities in Brazil, basic materials in Chile and the financial sector in Brazil. This research contributes to the literature by presenting a new panorama regarding the Latin American sectorial market environment, specifically the Brazilian, in periods of high volatility, as a way of effectively maximizing the eventual flow of resources in these economies.